Anti cancer activity of mangiferin from methanol extract of fruit of Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl.) - Ismail, Adawiah; Abdullah, Luqman Chuah; Pin, Kar Yong; Awang Biak, Dayang Radiah; Yusuf, Umi Kalsom; Ismail, Nor Fariza (UPM-MAKNA Cancer Research Laboratory, Institute of Bioscience, 2014)
Phaleria macrocarpa (Scheff.) Boerl known as Mahkota Dewa is one of Indonesia's traditional medicines from family of Thymelaeaceae. Traditional medicine practitioners claim that the chemical compounds in mahkota dewa retains antihistamine, antioxidant and anti cancer effects. In this study, one compound has been successfully isolated from methanolic extract of Mahkota Dewa's fruit as single compound known as mangiferin. To ensure whether this compound; mangiferin contribute to the anti cancer activities, the cytotoxic effect on a breast cancer cell line; MCF-7, cervical cancer cell line; HeLa, and human colon adenocarcinoma cell; HT-29, was examined. The results show that Mahkota Dewa can be promising sources of natural products with potential anti cancer.